2023
DOI: 10.1108/ijhma-04-2023-0054
|View full text |Cite
|
Sign up to set email alerts
|

Does urban tourism development impact urban housing prices?

Abstract: Purpose The purpose of this study is to investigate the relationship between tourism development and urban housing prices in Chinese cities. Specifically, the study aimed to explore whether there is a relationship between the two variables in tourist and non-tourist cities and whether there is a non-linear relationship between them. Design/methodology/approach In this study, the entropy method was used to construct the China City Tourism Development Index, which provides a more comprehensive measure of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…On the other hand, Tourism showed a negative, albeit statistically significant, coefficient. This supports the findings of Alola et al (2020) and Cong et al (2023), which suggest that tourism development suppresses urban housing prices. The growth of tourism may increase the supply of housing in an area to meet the demand for tourist accommodation.…”
Section: Baseline Regression Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, Tourism showed a negative, albeit statistically significant, coefficient. This supports the findings of Alola et al (2020) and Cong et al (2023), which suggest that tourism development suppresses urban housing prices. The growth of tourism may increase the supply of housing in an area to meet the demand for tourist accommodation.…”
Section: Baseline Regression Resultssupporting
confidence: 90%
“…Policy interventions and regulatory frameworks have profound implications for housing markets as well, as land-use constraints (Pollakowski & Wachter, 1990), home-purchase limits (Jia et al, 2018), foreign capital inflows and speculation (Wong et al, 2020), and political uncertainty (Nguyen & Vergara-Alert, 2023) can affect housing affordability and availability. Furthermore, urban development patterns such as tourism development (Cunha & Lobão, 2022;Cong et al, 2023) and urbanization level (Liu et al, 2022) also influence housing markets. Neighborhood characteristics such as railway sound barriers (Lee & Pang, 2022) impact property values and market demand as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because there could be underlying deficiencies in the study design, the observed impact of digital economy on income inequality based on the benchmark regression may be coincidental. To address this concern, a placebo test was conducted following the methodology described in Ding et al [ 60 ], Cong et al [ 61 ] and Cong et al [ 62 ]. In this test, all data was removed from the sample and then randomly reallocated before re-estimating the baseline test.…”
Section: Research Methodology and Datamentioning
confidence: 99%